An Integrated System for Managing and Evaluating Student Code Submissions - Tomasz GUTOWSKI (Communications of International Proceedings, 2025)
This paper presents the development and deployment of a web-based platform designed to improve the process of managing and evaluating programming assignments in academic setting. The system integrates three components: assignment creation, automated grading, and code similarity detection — all within a unified, user-friendly interface. Its primary objective is to reduce the time and effort required by teachers to assess large volumes of student submissions while maintaining fairness, consistency, and transparency in grading. The platform allows teachers to define assignments and corresponding test cases, which are then used for automatic evaluation of submitted code. The grading engine executes student programs in a secure environment and compares the outputs against expected results, providing detailed feedback for each test case. In addition, the system features a built-in similarity detection module that highlights pairs of potentially plagiarized solutions. This mechanism supports teachers in identifying dishonest practices while preserving students’ privacy and autonomy. The system was successfully implemented and tested in real university courses, where it demonstrated its practical value in improving both the efficiency of course management and the quality of student feedback. Teachers benefited from significantly reduced manual workload, and students gained faster access to consistent evaluations. While the platform currently supports a limited set of programming languages and uses a relatively simple similarity detection approach, it lays a solid foundation for further improvement. Overall, the developed solution contributes to modernizing programming education and addressing challenges in large-scale course delivery.
Keywords: Automated Grading; Code Similarity Detection; Programming Education; Education Technology